Burst Pressures in Eyes with Clear Corneal Incisions Treated with ReSure Glue - Ahmed E. M. Shehata; Siva P. Kambhampati; Jiangxia Wang; Uri S. Soiberman (Journal of Ophthalmology)
Purpose. This study aims to measure burst pressures in 3 mm clear corneal incisions sealed with ReSure, a biodegradable hydrogel sealant, and to compare it to traditional 10-0 nylon sutures and unsealed controls. Design. An ex vivo animal study. Methods. 3 mm clear corneal incisions were performed in rabbit eyes (ex vivo). The burst pressure was determined, and then, the incisions were sealed with either ReSure glue or a single 10-0 nylon suture. Burst pressure measurements were repeated. Results. Fourteen eyes were included. The median burst pressure in the suture-control group (7 eyes) prior to suture application was 7 mmHg (range: 0–45); the median burst pressure in the 7 glue-controls was 36 mmHg (range: 5–61, p = 0.08 for the comparison of the two control groups). The median burst pressure in the glue group was 93 mmHg (range: 39–129, p = 0.043 when compared to glue-control). The median burst pressure in the suture group was 158 mmHg (range: 70–180, p = 0.018 when compared to suture-control). There was no statistically significant difference in burst pressure values between the glue and suture groups (p = 0.08). Conclusion. In this study, ReSure glue applied to 3 mm clear corneal incisions provided sufficient resistance to elevated intraocular pressure when compared to controls. The results of this study suggest that ReSure glue may be comparable to a single 10-0 nylon suture in resisting fluid egress during the early postoperative period.